Intravenous abatacept in Japanese patients with polyarticular-course juvenile idiopathic arthritis: results from a phase III open-label study - Ryoki Hara; Hiroaki Umebayashi; Syuji Takei; Nami Okamoto; Naomi Iwata; Yuichi Yamasaki; Yasuo Nakagishi; Toshitaka Kizawa; Ichiro Kobayashi; Tomoyuki Imagawa; Noriko Kinjo; Norihito Amano; et al. (BMC, 2019)
Abstract Background To investigate efficacy and safety of intravenous abatacept in Japanese patients with active polyarticular-course juvenile idiopathic arthritis (pJIA). Methods In this phase III, open-label, multicenter, single-arm study, patients with pJIA aged 4-17 years who failed ≥1 biologic or methotrexate received weight-tiered (< 75 kg: 10 mg/kg; 75-100 kg: 750 mg; > 100 kg: 1000 mg) intravenous abatacept at Weeks 0, 2, 4, and every 4 weeks thereafter. The study comprised a short-term period (16 weeks) and ongoing long-term period. Primary endpoint: Week 16 JIA-American College of Rheumatology criteria 30 (JIA-ACR30) response rate. Secondary endpoints/outcomes included Week 16 JIA-ACR50/70/90 response and inactive disease rates, Childhood Health Assessment Questionnaire-Disability Index (CHAQ-DI), pharmacokinetics, safety, and immunogenicity. Proportions of patients achieving Juvenile Arthritis Disease Activity Score in 27 joints using C-reactive protein (JADAS27-CRP) remission (score < 1) and minimal disease activity (MDA; score < 3.8), were among exploratory endpoints. Results All 20 patients who received study medication completed the short-term period. During the long-term period, two patients discontinued due to insufficient efficacy or patient decision. Median age and disease duration at baseline were 10.5 and 0.75 years, respectively. Week 16 JIA-ACR30 response rate (primary endpoint) was 90.0% (18/20). JIA-ACR50/70/90 response and inactive disease rates at Week 16 were 75.0% (15/20), 70.0% (14/20), 35.0% (7/20), and 25.0% (5/20), respectively. At Week 52, JIA-ACR30/50/70/90 response and inactive disease rates were observed by 88.9% (16/18), 88.9% (16/18), 83.3% (15/18), 66.7% (12/18) and 44.4% (8/18), respectively. CHAQ-DI improved after Week 12. JADAS27-CRP remission and MDA were achieved by 15.0% (3/20) and 45.0% (9/20) of patients at Week 16, and by 50.0% (9/18) and 78.0% (14/18) of patients at Week 52, respectively. The mean abatacept pre-dose serum concentration was above the target therapeutic exposure (10 μg/ml) from Week 8 through Week 16. All adverse events were of mild/moderate intensity, except for one case of severe gastroenteritis. No deaths, malignancies, or autoimmune disorders were observed. No antidrug antibodies were detected through Week 16; one patient had a positive immunogenic response during the cumulative period. Conclusion Intravenous abatacept was efficacious and well tolerated in Japanese patients with active pJIA. Trial registration ClinicalTrials.gov: NCT01835470. Date of registration: April 19, 2013.